(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2008)
Our moral perspective should not be limited to the impartial concern for all who share a common humanity with us. It should also include the value of partiality embedded in personal relationships of love and friendship. These personal relationships give shape and meaning to our lives, and they also provide us with a sense of identity. The values that underpin our common humanity are based on the universal features of all human beings, including those who are strangers to us. On the other hand, our special relationships are dependent upon features that distinguish our friends and loved ones from others. These relationships grow out of shared experiences and commitments, and are the products of specific times and places. A balanced moral life will not seek to place one set of values over the other, but will instead have two distinct spheres for both an impartial love of humanity, as well as for the partialities of our particular attachments and special relationships.